Encyclopedic history of economic thought - Sampat Mukherjee (New central book agency, 2017)
Starting from the earliest concepts of economic thought from Aristotle and from the most precise concepts of microeconomics to the philosophies of free trade, this title discusses the ideas of more than 100 great thinkers and practitioners in the history of economic thought (or the evolution of economic doctrines) and focuses on different schools of thought which have fundamentally affected the way we live. The book gives a comprehensive coverage to all key ideas and fundamental concepts which emerged as the social science of economics or 'the queen of social sciences', a term coined by economists' economist Paul Samuelson, evolved over centuries.